2023
DOI: 10.3390/life13020403
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Pulmonary Rehabilitation in Patients with Idiopathic Pulmonary Fibrosis

Abstract: Background: This study evaluated the efficacy and safety of pulmonary rehabilitation (PR) on functional performance, exercise-related oxygen saturation, and health-related quality of life among patients with idiopathic pulmonary fibrosis (IPF). Methods: A total of 25 patients with IPF (13 in the PR group and 12 in the non-PR group) were enrolled between August 2019 and October 2021 at Haeundae-Paik Hospital in the Republic of Korea. A cardiopulmonary exercise test (CPET), six-minute walk test (6MWT), pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In concurrent with current study, Choi et al [17] did not confirm any improvement in PFT [FVC] variables values between the groups after eight weeks of PR on 25 patients with IPF, also reported the significant improvement in 6MWT values after PR in the PR group with p value = 0.002. Also, Sciriha et al [18] reported; after 12 weeks of Pulmonary Rehabilitation program for 60 patients with ILDs resulted in significant improvement in 6MWT [P value = 0.001] and no significant changes were found in FVC [p = 0.832].…”
Section: Discussionsupporting
confidence: 54%
“…In concurrent with current study, Choi et al [17] did not confirm any improvement in PFT [FVC] variables values between the groups after eight weeks of PR on 25 patients with IPF, also reported the significant improvement in 6MWT values after PR in the PR group with p value = 0.002. Also, Sciriha et al [18] reported; after 12 weeks of Pulmonary Rehabilitation program for 60 patients with ILDs resulted in significant improvement in 6MWT [P value = 0.001] and no significant changes were found in FVC [p = 0.832].…”
Section: Discussionsupporting
confidence: 54%
“…Choi et al [23] compared two groups of IPF patients, of which one underwent PR, with significant improvements in the 6MWD in the interventional group at the end of PR. Exercise programmes also improved the maximum oxygen consumption (VO 2 max) measured by the cardiopulmonary test (CPET), an indicator of maximal exertion levels.…”
Section: The Impact Of Pr On Exercise Capacitymentioning
confidence: 99%
“…Moreover, PR can take place in different settings, thus affecting the adherence degree of the patient as well as the overall effectiveness of the therapy. Most of the studies so far included in this review took place in a supervised outpatient [22,23,25,27,[31][32][33][34]49] or inpatient [28] setting, while only a few were conducted as home-based [24,33,35] or combined [26,29] PR programmes. Home-based PR is a self-care-based, mostly unsupervised intervention in which the physiotherapist provides a training scheme and the participants perform the PR exercise by themselves.…”
Section: Which Are the Most Appropriate Settings And Programmes For P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies [30][31][32][33][34][35][36][37][38][39] were included in this systematic review. Of these, four were randomized controlled trials [31][32][33][34], five were quasi-experimental trials [30,32,[34][35][36], and one was a pilot study [33].…”
Section: Study Selectionmentioning
confidence: 99%